Pengaruh Layanan Bimbingan Kelompok dengan Teknik Self Management untuk Meningkatkan Kemandirian Belajar Siswa - Nadhrotul Qurrota Aini; Mahdum Free Unita Mahdum; Kiki Mariah (Jurnal Ilmiah Dikdaya, 2026)
This study aims to determine the influence of group guidance services with self-management techniques on increasing the learning independence of SMP Negeri 8 Pekanbaru students. The approach used is quantitative with the One Group Pretest-Posttest Design experimental design. The research sample consisted of 9 grade VIII students who had a low level of learning independence based on the results of the initial questionnaire. Data collection was carried out using a Liker-based learning independence scale which included five main aspects: self-motivation, time management, learning strategies, critical thinking skills, and social and emotional skills. Data analysis was carried out through the Wilcoxon test and the normalized N-Gain test . The results showed a significant increase in students' learning independence after being provided with group guidance services with self-management techniques, with an Asymp. Sig. (2-tailed) value of 0.008 (< 0.05) and an average N-Gain score  of 0.59 which was in the medium category. All aspects of learning independence have increased, especially in self-motivation (38.89%) and learning strategies (33.34%). These findings show that the application of group tutoring services with self-management techniques is effective in helping students develop the ability to organize, control, and motivate themselves to learn independently, disciplinedly, and responsibly for their learning process.